2003
DOI: 10.1097/01.tp.0000046942.02001.26
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant administration of allochimeric major histocompatibility complex class-I-molecules induces true transplantation tolerance

Abstract: Allochimeric MHC class-I therapy is a unique and novel clinically applicable approach for induction of "true" transplantation tolerance where chronic rejection is concomitantly abrogated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…generated NKT cells post-transplant, either by prolonging subtherapeutic doses of FK506 or by continuous oral antigen ingestion, can prolong allograft survival even further. This would be consistent with reports that prolonged administration of post-transplant MHC molecules and subtherapeutic cyclosporine A or intraportal donor-specific blood transfusion prolong allograft survival [58,59].…”
Section: Figsupporting
confidence: 88%
“…generated NKT cells post-transplant, either by prolonging subtherapeutic doses of FK506 or by continuous oral antigen ingestion, can prolong allograft survival even further. This would be consistent with reports that prolonged administration of post-transplant MHC molecules and subtherapeutic cyclosporine A or intraportal donor-specific blood transfusion prolong allograft survival [58,59].…”
Section: Figsupporting
confidence: 88%
“…Our studies imply an important role for both donor immunogenic epitopes a well as self-epitopes in peripheral transplantation tolerance by peritransplant administration since portal venous administration of either whole donor or recipient non-mutated class I antigens have not resulted in long-term allograft acceptance [25,41]. Concurrent presentation of self and dominant donor determinants, may have downmodulated the immune response to donor cardiac allografts.…”
Section: Discussionmentioning
confidence: 74%
“…Cytokines analysis of long-term allografts revealed selective upregulation of IL-10, but marked inhibition of IL-2, IFN-γ, and IL-4. Furthermore, long-term allografts in allochimeric-conditioned hosts exhibited moderate B cell infiltration, limited monocyte and absent CD8 + cells [6][7][8][9]. In addition, our adoptive transfer studies showed that the secondary cardiac grafts from recipients exposed to allochimeric MHC I-conditioned splenic total T cells or CD4 + T cells showed significantly reduced neointimal index (NI) and apoptosis, and were selectively infiltrated with CD4 + Foxp3 + (T regulatory, Treg) cells [10].…”
Section: Introductionmentioning
confidence: 78%
“…Adult male inbred Wistar Furth (WF; RT1.A u ) and ACI (RT1.A a ) rats were purchased from Harlan Sprague Dawley (Indianapolis, IN) and housed in standard rat cages. Heterotopic cardiac transplants were placed intraabdominally as described previously [6][7][8][9][10][11][12][13][14][15]. Transplantation was performed as follows: 1) transplantation control group that received no treatment; 2) transplantation in the presence of high dose cyclosporine (CsA) delivered by gavage feed (10 mg/kg, day 0 -6); 3) transplantation in the presence of sub-therapeutic dose of CsA delivered by gavage (10 mg/kg, day 0 -2); 4) transplantation in the presence of Y-27632 inhibitor (Fisher Scientific, 2 mg/kg, day 0 -6) delivered by gavage; and 5) transplantation in the presence of sub-therapeutic dose of CsA (10 mg/kg, day 0 -2) in conjunction with Y-27632 inhibitor (2 mg/kg) which was gavage fed as a single dose before the transplantation.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation